Pembatalan Sertifikat Hak Milik Atas Tanah - Wa Ode Hasbia; Adonia Ivone Laturette; Sabri Fataruba (Faculty of Law, Universitas Pattimura, 2021)
Introduction: The certificate of the cancellation of the land ownership is the cancellation of the rights of land because the right receiver doesn’t fulfill the qualifications that be setted.Purposes of the Research: To analize and Study juridically, the accuracy of the certificate cancellation of the land ownership Number 345 Year 2002 in Batu Merah village, Sirimau District, Ambon City, dan to analize and study the legal effort from the owner of the certificate of land ownership Number 345 Year 2p02 di Batu Merah village, Sirimau District, Ambon city.Methods of the Research: This observation is a normative observation, which study the clauses of positive law, law principles, or doctrine to answer the law issues that be faced.Results of the Research: This observation shows that the cancellation of the land ownership procedures have judex jures law with the existence of Peraturan Daerah Provinsi Maluku Number 10 Year 2005 About Penetapan Daerah Negeri sebagai kesatuan masyarakat ukum adat di negeri batu merah, and on the certificate factors Number 345 Year 2002 That Badan Pertanahan Nasional (National Land Agency) has Setted the Putusan Mahkamah Agung Number 305 PK/Pdt/2016.